Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Sure! Let's go through the process of finding the derivative of the function [tex]\( f(x) = (10 x^2 + 2 x + 3) (8 x^{-4} - 2 x + 3)^3 \)[/tex].
Step 1: Define the Function
Given:
[tex]\[ f(x) = (10 x^2 + 2 x + 3)(8 x^{-4} - 2 x + 3)^3 \][/tex]
Step 2: Apply the Product Rule
To differentiate [tex]\( f(x) \)[/tex], we need to use the product rule which states:
[tex]\[ (uv)' = u'v + uv' \][/tex]
Here, let
[tex]\[ u = 10 x^2 + 2 x + 3 \][/tex]
[tex]\[ v = (8 x^{-4} - 2 x + 3)^3 \][/tex]
To apply the product rule, we need to first find [tex]\( u' \)[/tex] and [tex]\( v' \)[/tex].
Step 3: Differentiate [tex]\( u \)[/tex]
[tex]\[ u = 10 x^2 + 2 x + 3 \][/tex]
[tex]\[ u' = \frac{d}{dx}(10 x^2) + \frac{d}{dx}(2 x) + \frac{d}{dx}(3) \][/tex]
[tex]\[ u' = 20 x + 2 + 0 \][/tex]
[tex]\[ u' = 20 x + 2 \][/tex]
Step 4: Differentiate [tex]\( v \)[/tex] using the Chain Rule
[tex]\[ v = (8 x^{-4} - 2 x + 3)^3 \][/tex]
Let
[tex]\[ g(x) = 8 x^{-4} - 2 x + 3 \][/tex]
Then
[tex]\[ v = [g(x)]^3 \][/tex]
Using the chain rule:
[tex]\[ v' = 3 [g(x)]^2 g'(x) \][/tex]
First, find [tex]\( g'(x) \)[/tex]:
[tex]\[ g(x) = 8 x^{-4} - 2 x + 3 \][/tex]
Differentiate term-by-term:
[tex]\[ g'(x) = \frac{d}{dx}(8 x^{-4}) + \frac{d}{dx}(-2 x) + \frac{d}{dx}(3) \][/tex]
[tex]\[ g'(x) = 8(-4)x^{-5} - 2 + 0 \][/tex]
[tex]\[ g'(x) = -32 x^{-5} - 2 \][/tex]
So,
[tex]\[ v' = 3 (8 x^{-4} - 2 x + 3)^2 (-32 x^{-5} - 2) \][/tex]
Step 5: Combine using the Product Rule
Combine [tex]\( u' \)[/tex] and [tex]\( v' \)[/tex] using the product rule:
[tex]\[ f'(x) = u' v + u v' \][/tex]
Letting:
[tex]\[ u = 10 x^2 + 2 x + 3 \][/tex]
[tex]\[ u' = 20 x + 2 \][/tex]
[tex]\[ v = (8 x^{-4} - 2 x + 3)^3 \][/tex]
[tex]\[ v' = 3 (8 x^{-4} - 2 x + 3)^2 (-32 x^{-5} - 2) \][/tex]
We get:
[tex]\[ f'(x) = (20 x + 2)(8 x^{-4} - 2 x + 3)^3 + (10 x^2 + 2 x + 3) \cdot 3 (8 x^{-4} - 2 x + 3)^2 (-32 x^{-5} - 2) \][/tex]
Step 6: Simplify the Expression
After combining and simplifying the terms, the final expression for the derivative is:
[tex]\[ f'(x) = \frac{2 (x^4 (3 - 2 x) + 8)^2 \left[ x (10 x + 1)(x^4 (3 - 2 x) + 8) - 3 (x^5 + 16) (10 x^2 + 2 x + 3) \right]}{x^{13}} \][/tex]
This is the derivation in simplified form, expressed with appropriate positive and negative exponents, and all without using radicals.
Step 1: Define the Function
Given:
[tex]\[ f(x) = (10 x^2 + 2 x + 3)(8 x^{-4} - 2 x + 3)^3 \][/tex]
Step 2: Apply the Product Rule
To differentiate [tex]\( f(x) \)[/tex], we need to use the product rule which states:
[tex]\[ (uv)' = u'v + uv' \][/tex]
Here, let
[tex]\[ u = 10 x^2 + 2 x + 3 \][/tex]
[tex]\[ v = (8 x^{-4} - 2 x + 3)^3 \][/tex]
To apply the product rule, we need to first find [tex]\( u' \)[/tex] and [tex]\( v' \)[/tex].
Step 3: Differentiate [tex]\( u \)[/tex]
[tex]\[ u = 10 x^2 + 2 x + 3 \][/tex]
[tex]\[ u' = \frac{d}{dx}(10 x^2) + \frac{d}{dx}(2 x) + \frac{d}{dx}(3) \][/tex]
[tex]\[ u' = 20 x + 2 + 0 \][/tex]
[tex]\[ u' = 20 x + 2 \][/tex]
Step 4: Differentiate [tex]\( v \)[/tex] using the Chain Rule
[tex]\[ v = (8 x^{-4} - 2 x + 3)^3 \][/tex]
Let
[tex]\[ g(x) = 8 x^{-4} - 2 x + 3 \][/tex]
Then
[tex]\[ v = [g(x)]^3 \][/tex]
Using the chain rule:
[tex]\[ v' = 3 [g(x)]^2 g'(x) \][/tex]
First, find [tex]\( g'(x) \)[/tex]:
[tex]\[ g(x) = 8 x^{-4} - 2 x + 3 \][/tex]
Differentiate term-by-term:
[tex]\[ g'(x) = \frac{d}{dx}(8 x^{-4}) + \frac{d}{dx}(-2 x) + \frac{d}{dx}(3) \][/tex]
[tex]\[ g'(x) = 8(-4)x^{-5} - 2 + 0 \][/tex]
[tex]\[ g'(x) = -32 x^{-5} - 2 \][/tex]
So,
[tex]\[ v' = 3 (8 x^{-4} - 2 x + 3)^2 (-32 x^{-5} - 2) \][/tex]
Step 5: Combine using the Product Rule
Combine [tex]\( u' \)[/tex] and [tex]\( v' \)[/tex] using the product rule:
[tex]\[ f'(x) = u' v + u v' \][/tex]
Letting:
[tex]\[ u = 10 x^2 + 2 x + 3 \][/tex]
[tex]\[ u' = 20 x + 2 \][/tex]
[tex]\[ v = (8 x^{-4} - 2 x + 3)^3 \][/tex]
[tex]\[ v' = 3 (8 x^{-4} - 2 x + 3)^2 (-32 x^{-5} - 2) \][/tex]
We get:
[tex]\[ f'(x) = (20 x + 2)(8 x^{-4} - 2 x + 3)^3 + (10 x^2 + 2 x + 3) \cdot 3 (8 x^{-4} - 2 x + 3)^2 (-32 x^{-5} - 2) \][/tex]
Step 6: Simplify the Expression
After combining and simplifying the terms, the final expression for the derivative is:
[tex]\[ f'(x) = \frac{2 (x^4 (3 - 2 x) + 8)^2 \left[ x (10 x + 1)(x^4 (3 - 2 x) + 8) - 3 (x^5 + 16) (10 x^2 + 2 x + 3) \right]}{x^{13}} \][/tex]
This is the derivation in simplified form, expressed with appropriate positive and negative exponents, and all without using radicals.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.